Pengembangan Media Alphabet Tracking Board Untuk Meningkatkan Kemampuan Menulis Pada Anak Kelompok B - Miftah Trihastuti; Arwendis Wijayanti; Wening Sekar Kusuma (NANAEKE: Indonesian Journal on Early Childhood Education, 2023)
Early childhood education is crucial for children aged 0-8, focusing on physical, intelligence, thinking, creativity, emotional, spiritual, language/communication, and social development. Teaching writing from a young age is essential for human communication. However, over 75% of children in group B struggle with writing skills due to traditional learning media, causing boredom and lazy completion. This study aims to determine the effectiveness of using Alphabet Tracking Board as a media to improve the writing skills of children in group B. Learning activities for early childhood usually involve play, and writing is considered a fundamental communication skill that needs to be taught at an early age. If children do not understand letters properly, it can hinder their interactions with other individuals or groups. However, observations of 7 children in TK Garuda Sakti and 15 children in TK Paramadinah from group B showed that their writing skills have not developed well. Therefore, the researcher developed a new innovation in the form of Alphabet Tracking Board as a solution. This media is suitable for the study as the main material, Javanese teak wood, is easy to find in the research area. The Alphabet Tracking Board is a new development of media innovation to enhance children's writing skills, developed through the ADDIE process (Analysis, Design, Development, Implementation, and Evaluation). Based on the validation results, the Alphabet Tracking Board has a validity percentage of 91.34%, which is within the achievement criteria of 81.00% - 100%, indicating that the media is highly valid and can be used without revision.